MENINGKATKAN HASIL BELAJAR LAY UP SHOOT MENGGUNAKAN METODE TUTORIAL TEMAN SEBAYA - Fitriansah, Ady Rochman (Journal of Sport Coaching and Physical Education, 2016)
The purpose of this research is the use of methods Tutorial Peers can improve learning outcomes lay up technique shoot basketball in class XI TKJ 1 in SMK Negeri 1 Bawang 2015.This research method is a Class Action Research (Classroom Action Research) action research procedure includes the planning stage (planning), the implementation phase (action), the stage of observation (observation), and the stage of reflection (reflection). Data was collected by conducting field observations (observation), interviews and documentation. The instruments used were the syllabus, lesson plans, and assessment instruments that include affective, cognitive and psychomotor. Analysis of the data used is a qualitative description.Classical mastery learning to be achieved by learning Lay Up Shoot is 75%. Classical mastery learning value in the first cycle reaches 73.77% (unfinished). While the value of classical learning completeness in the second cycle reaches 83.40% (completed). Improving student learning outcomes after having a second cycle (gain) of 0.8 with high criteria.The conclusions of this study is there is an increase in learning outcomes in learning the lay-up shoot using the tutorial peers in class XI TKJ 1 SMK 1 Bawang 2015.